Growth, structural, spectral, thermal, mechanical, electrical, linear and third order nonlinear optical properties of Imidazolium hydrogen maleate (IM) single crystal for nonlinear optical applications. (13th March 2019) - Elangovan, K; Senthil, A
Abstract: Optically good quality single crystals of Imidazolium hydrogen maleate (IM) were grown by slow evaporation solution technique method (SEST) at 30 °C. The formation of a crystalline compound was determined by single crystal XRD analysis. The Imidazolium hydrogen maleate was crystallized in monoclinic crystal system with a centrosymmetric space group P21 /c. The crystalline nature was analyzed by powder XRD study. Irreducible representation was given for the crystal and using the FTIR and FT-Raman techniques the functional groups present in the title molecule was identified. UV–vis-NIR transmittance spectral analysis was adopted to obtain the optical properties of the crystal and the cut-off wavelength was observed at 320 nm with high transmittance. Thermal properties of the compound have been investigated by thermogravimetric (TG/DTG) and differential scanning calorimetry (DSC) studies. The mechanical properties of the crystal were carried out effectively by Vickers microhardness study. Dielectric studies as a function of different frequencies was carried out at 30 °C temperature. The third order nonlinear optical properties of the crystal were measured such as nonlinear refractive index (n2 ) and nonlinear absorption coefficient ( β ) and were investigated. The third order nonlinear optical susceptibility ( χ (3) ) as found to be 5.764 × 10 −9 esu.